International experience of advanced countries in state management of countering hybrid threats - KHMYROV, Ihor; KHRIAPYNSKYI, Anton; ALIIEVA, Polina; KOPOTUN, Igor; SVOBODA, Ivo (Revista Jurídica Portucalense, 2024)
Hybrid threats combine various instruments of influence, from traditional military operations to cyberattacks and disinformation activities. These threats severely challenge states' national security and require an adequate response from public authorities. The study examines the experience and the existing approaches of the world's leading countries in the state management of countering hybrid threats. The research methods employed in this study were comprehensive, including a graphical analysis of country profiles, a detailed comparison of international ratings and indices, the basic indicator approach, and an in-depth analysis of strategic documents of individual countries and associations. This comprehensive approach has provided a detailed understanding of the leading countries' main institutional mechanisms, strategies, and measures to counter hybrid warfare, instilling confidence in the study's findings. The study's findings underscore the necessity for an integrated approach to countering hybrid threats and close coordination between different agencies at the national level. The results show that leading countries use specialised structures to coordinate efforts, strengthen cooperation between government agencies and the private and public sectors, implement measures to ensure cybersecurity and protect critical infrastructure, and intensify international cooperation. Recommendations for improving critical infrastructure protection, developing a comprehensive strategy, and strengthening international collaboration are substantiated.